Kompensasi bagi Manajemen: Pengaruh terhadap Kinerja Organisasi - M. Rafi Fajar Ifandi; M. Sadam Putra Bilal; M. Rizky Saputra; Yudha Prawira; Wahyu Nur Cahyo (Jejak digital: Jurnal Ilmiah Multidisiplin, 2025)
Management compensation is the financial and non-financial rewards provided by companies for managing operations to ensure business continuity. This compensation includes base salary, performance bonuses, and allowances, which influence managers’ motivation to improve organizational performance. This study uses library research methods from Google Scholar to analyze the effect of management compensation on company effectiveness. The results show that appropriate compensation has a significant positive effect on current and subsequent year performance, contributing up to 41.8% to increased productivity. Implication: Companies need to design performance-based compensation structures to attract and retain quality managers